Screening of cognitive performance in kidney transplant recipients: a mini review - Schietzel, Simeon; Kressig, Reto W.; Huynh-Do, Uyen (Frontiers in Nephrology, 2023)
Why should we screen? The prevalence of cognitive impairment in kidney transplant recipients (KTRs) is up to 58%. The 10-year graft loss and mortality rates are above 30% and 50%, respectively, and executive malfunctioning increases disadvantageous outcomes. What causes cognitive impairment in KTRs? Strong risk factors are older age and chronic kidney disease. However, causes are multifactorial and include cardiovascular, cerebrovascular, neurodegenerative, inflammatory, uremic, psychiatric, and lifestyle-related susceptibilities. How should we screen? KTR-specific validated instruments or strategies do not exist. The central element should be a multidomain cognitive screening test that is sensitive to mild cognitive impairment, corrects for age and education, and includes executive functions testing. Cognitive trajectories, effects on everyday life and psychiatric comorbidities should be assessed by integrating the perspectives of both patients and knowledgeable informants. When should we screen? Screening should not be postponed if there is suspicion of impaired cognition. Different time points after transplantation tend to have their own characteristics. Who should conduct the screening? Screening should not be limited to specialists. It can be carried out by any healthcare professional who has received a limited amount of training. What are the benefits of screening? Screening does not provide a diagnosis. However, suggestive results change care in multiple ways. Goals are: Initiation of professional dementia work-up, securing of adherence, anticipation of potential complications (delirium, falls, frailty, functional impairment, malnutrition, etc.), mitigation of behavioral disorders, adjustment of diagnostic and therapeutic “load”, reduction of caregiver burden and meeting of changing needs. We summarize data on the prevalence, risk factors and sequelae of cognitive impairment in KTRs. We also discuss the requirements for appropriate screening strategies and provide guiding principles regarding appropriate and safe care.